Novel algorithm of traffic signals adaptive control on urban roads intersections - Zhang, Huanjiong (Journal of highway and transportation research and development, 2025)
The control of traffic flows on urban roads intersections through the traffic control signals is very important, not only does the jammed traffic statement valuably relieve and the ratio of the traffic availability increase, but also the traffic accidents evidently decrease. In this paper, an adaptive algorithm of traffic control signals on the urban roads intersections is designed in , this new algorithm can actively adjust the concrete control times of the traffic control signals based on the perceiving information of the waiting vehicles in real time, then the dynamic balance between the traffic control signals and the traffic flows can be realized. Furthermore, through experiment testing and demonstrating, this adaptive algorithm expresses some fine performances, it also shows good application prospect in the field of smart city.